Pendampingan Literasi untuk Komunitas Pembinaan Kesejahteraan Keluarga (PKK) Dukuh Kupang - Naila, Ishmatun; Kusumajanti, Wahju; Ridlwan, Muhammad; Haq, Muhamad Amirul (Khidmatuna: Jurnal Pengabdian Masyarakat, 2025)
Understanding and communicating stories is one of the fundamental literacy skills needed by the Dukuh Kupang PKK (Family Welfare Empowerment) group. These problems create obstacles in optimising the activities carried out and hinder the creation of innovations to improve the PKK program. The purpose of this service is to help PKK Dukuh Kupang members improve basic literacy skills, especially reading comprehension, comprehension and communication skills through storytelling competitions. The methods used include observation to investigate the problem, collaboration with stakeholders, conducting public relations activities, holding a competition, establishing a sustainability programme, and monitoring and evaluation. Thanks to this service, the literacy level of PKK cadres who participated in the short story writing competition increased significantly. This can be seen from the comparison of the ability to understand information and communication before and after the convention of 20 administrators representing Dukuh Kupang Sub-district. This increase in ability is related to storytelling competition metrics such as narrative weight (30%), rhetoric (30%), language and communication (20%), and creativity (20%). Based on the evaluation results, all teams as participants obtained the lowest score (85%) with the category "Good". In addition, this programme will also result in a strong and strategic cooperation with the Kapanewong Beruba government to implement charitable programmes related to improving the literacy skills of PKK cadres in the future.